A case for aid : building a consensus for development assistance : includes a "partnership for development and peace" by James D. Wolfensohn. - World Bank. (Washington, D.C. ; [Great Britain] : World Bank, 2002)
The book discusses the key issues at debate over aid to the world's poorest countries. it includes readings related to the United Nations International Conference on Financing for Development, Held in Monterrey, Mexico,in March 2002.
Selection of readings related to the United Nations International Conference on Financing for December, held in Monterrey, Mexico, March 18-22, 2002.
Includes bibliographical references.
opc 30/03/15, ijb 21/02/2019
Loans
Keywords: Economic assistance; Consensus (Social sciences)